Endothelin-1 stimulates the in vitro release of neurohypophyseal hormones, but not corticotropin-releasing hormone, via ETA receptors. - Yasin, S; Costa, A; Navarra, P; Pozzoli, G; Kostoglou-Athanassiou, I; Forsling, M; Grossman, A (1994)
The endothelins consist of a family of vasoconstrictor peptides originally isolated from endothelial tissue which are now known to be involved in neuroendocrine regulation. However, while there are data indicating the involvement of endothelins in the modulation of the hypothalamo-pituitary-adrenal (HPA) axis, the precise mechanisms involved have been unclear. We have therefore used a previously validated rat hypothalamic explant system in order to investigate the possible modulation of the neurohypophyseal hormones vasopressin and oxytocin, and corticotropin-releasing hormone (CRH), by endothelin-1 (ET-1) and endothelin-3 (ET-3). Following a period of stabilisation, the release of vasopressin, oxytocin and CRH remained approximately constant in successive 20-min incubations. Addition of ET-1 stimulated the release of vasopressin at a dose of 0.1 nmol/l (p < 0.05), and both vasopressin and oxytocin at 10 nmol/l (p < 0.01 and 0.05, respectively). The release of vasopressin and oxytocin induced by 10 nmol/l ET-1 were both totally blocked by co-incubation with either 1 or 10 mumol/l of the specific ETA receptor subtype antagonist cyclo (D-Trp-D-Asp-Pro-D-Val-Leu) (BQ-123). ET-1 had no effect on CRH release in the dose range of 0.1-1,000 nmol/l. In case any possible stimulation of CRH might be masked by simultaneous generation of nitric oxide (NO), an inhibitor of CRH secretion, addition of ET-1 was also carried out in the presence of the NO synthase inhibitor, L-NO-Arg: ET-1 was again without effect in this dose range.(ABSTRACT TRUNCATED AT 250 WORDS)